Development and Validation of a Pediatric MRI-Based Perianal Crohn Disease (PEMPAC) Index—A Report from the ImageKids Study. Issue 5 (21st June 2021) - Choshen, Sapir; Turner, Dan; Pratt, Li-Tal; Precel, Ronit; Greer, Mary-Louise; Castro, Denise A; Assa, Amit; Martínez-León, María I; Herman-Sucharska, Izabela; Coppenrath, Eva; Konen, Osnat; Davila, Jorge; et al.
Abstract: Background: As part of the prospective multicenter ImageKids study, we aimed to develop and validate the pediatric MRI-based perianal Crohn disease (PEMPAC) index. Methods: Children with Crohn disease with any clinical perianal findings underwent pelvic magnetic resonance imaging at 21 sites globally. The site radiologist and 2 central radiologists provided a radiologist global assessment (RGA) on a 100 mm visual analog scale and scored the items selected by a Delphi group of 35 international radiologists and a review of the literature. Two weighted multivariable statistical models were constructed against the RGA. Results: Eighty children underwent 95 pelvic magnetic resonance imaging scans; 64 were used for derivation and 31 for validation. The following items were included: fistula number, location, length and T2 hyperintensity; abscesses; rectal wall involvement; and fistula branching. The last 2 items had negative beta scores and thus were excluded in a contending basic model. In the validation cohort, the full and the basic models had the same strong correlation with the RGA ( r  = 0.75; P  < 0.01) and with the adult Van Assche index (VAI; r  = 0.93 and 0.92; P  < 0.001). The correlation of the VAI with the RGA was similar ( r  = 0.77; P  < 0.01). The 2 models and the VAI had a similar ability to differentiate remission from active disease (area under the receiver operating characteristic curve, 0.91-0.94). The PEMPAC index had good responsiveness to change (area under the receiver operating characteristic curve, 0.89; 95% confidence interval, 0.69-1.00). Conclusions: Using a blended judgmental and mathematical approach, we developed and validated an index for quantifying the severity of perianal disease in children with CD. The adult VAI may also be used with confidence in children.